STARTING A NEW MEDICINE STUDY. Issue 9 (17th August 2016) - Aston, Jeff; Wilson, Keith; Terry, David
Abstract : Aim: To identify the experiences of patients, parents or carers when a child/young person is prescribed a new long-term medicine. Method: Patients' prescribed a new long-term (>6 weeks) medicine were recruited from a single UK paediatric hospital out-patient pharmacy. A semi-structured questionnaire was administered to participants, via telephone, 6 weeks after the dispensing of their medicine. The questionnaire included the following themes: information requirements, resources used to seek further information, medicine administration issues, new concerns or questions that have arisen, adverse effects, arranging repeat supplies and an assessment of adherence. The results were analysed using Microsoft Excel 2013 and NVivo Version 10. Results: Fifty patients consented and were included in the study. Eighteen (36%) participants had undertaken further research prior to taking/administering their new medicine. 13 (72%) of these used the internet for further information. Participants had further concerns/questions in 18 (36%) cases with 7 (38.9%) contacting the hospital team for further advice. Thirteen (26%) participants experienced difficulty administering/taking the medicine. Sixteen (36%) believed that they had experienced an adverse effect. Eight (16%) participants experienced difficulties when obtaining further supplies. With regard to adherence, 17 (34%) participants had forgotten a dose on at least one occasion and 4 (8%) found it difficult to keep to the medication regimen. Conclusion: This research has demonstrated that paediatric patients, parents and carers experience a wide range of issues during the first few weeks after starting a new medicine. This is in accordance with a recent review of non-adherence in paediatric long-term medical conditions.1 The New Medicines Service (NMS) offered through community pharmacists is designed to support patients' who have recently been prescribed a medicine to manage a long-term condition.2 However, this is not readily available to children/young people or their carers. The main barriers being the targeted conditions included in the service, consent and exclusion of undertaking an NMS consultation with a carer. Further research is required to establish and evaluate a paediatric specific medication review service for children/young people and their parents/carers when a new long-term medicine has been prescribed. This research will support the recent research recommendation of the National Institute of Health and Care Excellence.3